(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Effective communication is crucial in various domains, including academic, professional, and social settings. Developing a comprehensive understanding and proficiency in diverse speech types greatly enhances an individual’s capacity to engage, inform, and influence audiences. This article investigates the four primary speech types in English—informative, persuasive, demonstrative, and entertaining—and provides actionable techniques for delivering each type with efficacy. It details strategies related to speech structuring, audience interaction, and non-verbal cues, allowing speakers to tailor their presentations according to context and audience demands. Additionally, this paper highlights how mastering these methods fosters confidence and maximizes the impact of public speaking.